Posterior Uterine Rupture Causing Fetal Expulsion into the Abdominal Cavity: A Rare Case of Neonatal Survival - K. Navaratnam; P. Ulaganathan; M. A. Akhtar; S. D. Sharma; M. G. Davies (Case Reports in Obstetrics and Gynecology)
Introduction. Uterine rupture is a potentially catastrophic complication of vaginal birth after caesarean section. We describe the sixth case of posterior uterine rupture, with intact lower segment scar, and the first neonatal survival after expulsion into the abdominal cavity with posterior rupture. Case Presentation. A multiparous woman underwent prostaglandin induction of labour for postmaturity, after one previous caesarean section. Emergency caesarean section for bradycardia revealed a complete posterior uterine rupture, with fetal and placental expulsion. Upon delivery, the baby required inflation breaths only. The patient required a subtotal hysterectomy but returned home on day 5 postnatally with her healthy baby. Discussion. Vaginal birth after caesarean section constitutes a trial of labour, and the obstetrician must be reactive to labour events. Posterior uterine rupture is extremely rare and may occur without conventional signs. Good maternal and fetal outcome is possible with a prompt, coordinated team response.